Fine mapping of the major gene BhHLS1 controlling seed size in wax gourd (Benincasa hispida) - Yang, Wenrui; Wang, Peng; Liu, Ting; Nong, Lifeng; Cheng, Zhikui; Su, Liwen; Bai, Wenhui; Deng, Yan; Chen, Zhihao; Liu, Zhengguo (Frontiers in Plant Science, 2023)
The seed size of wax gourds is an important agronomic trait; however, the associated genes have not yet been reported. In this study, we used a high-density genetic map constructed based on F8 recombinant inbred line populations derived from a cross between MY-1 (large seed) and GX-71 (small seed) strains to detect quantitative trait locis (QTLs) for seed-size-related traits in wax gourd over a twoyear period. Two stable QTLs major quantitative trait locis (qSL10 and qSW10) for seed length (SL) and seed width (SW) on chromosome 10 were repeatedly detected over two years (2021)(2022). qSL10 had a phenotypic variation rate of 75.30% and 80.80% in 2021 and 2022, respectively. Whereas, qSW10 had a phenotypic variation rate of 66.60% and 73.80% in 2021 and 2022, respectively. Further, a single nucleotide polymorphism mutation was found to cause early termination of Bch10G006400 (BhHLS1) translation in GX-71 through sequencing analysis of candidate genes. Based on gene functional annotation and quantitative real-time PCR analyses, BhHLS1 encoded a probable N-acetyltransferase HLS1-like protein and its expression level was significantly different between parents. Therefore, BhHLS1 is a major candidate gene associated with a one-factor polymorphism regulating the SL and SW of wax gourds. Finally, based on variation in the BhHLS1 sequence, a cleaved amplified polymorphic sequence marker was developed for the molecular marker-assisted breeding of wax gourds. Overall, this study is of great significance for the genetic improvement of seed size, verification of gene functions, and cultivation of specific germplasm resources for wax gourds.